Engineering light-responsive enzymes for sensitive optogenetic control of biofilm dynamics - Teng, Aloysius Min Ren (Nanyang Technological University, 2024)
Biofilms are one of the most widely distributed modes of life on Earth and have been found to be involved in the geochemical cycles of water, soil, and subsurface environments. The use of biofilm-mediated bioprocesses for various biotechnological applications has been explored due to the easier process control of immobilized biofilms and protection from physicochemical stresses conferred by the biofilm matrix. However, to utilise these beneficial biofilms effectively and efficiently, it is important to engineer a controllable biofilm so that an optimal biofilm thickness can be maintained in these engineered systems. This can be accomplished with optogenetic tools that target the intracellular dynamics of bis-(3’-5’)-cyclic dimeric guanosine monophosphate (c-di-GMP), a ubiquitous nucleotide second messenger that has been found to play a vital role between the switch from the motile and sessile modes of life in bacteria.